2021
DOI: 10.1149/ma2021-0271834mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Designing Electrospun Composite Carbon Nanofiber (CNF) Photoelectrodes for Photoelectrochemical Transformation of Emerging Drinking Water Pollutants

Abstract: Novel nanomaterials, such as carbon nanofibers (CNFs), present a unique opportunity to advance photoelectrochemical drinking water treatment by integrating a photocatalyst to improve material properties and performance. To this end, we have fabricated electrospun CNF-TiO2 composite photoelectrodes with high surface area, conductivity, chemical stability, and mechanical strength for use in photoelectrochemical water treatment applications. The CNF-TiO2 physical, chemical, and electrical properties can be tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…S.3 ) ( Greenstein et al, 2021 ; Peter et al, 2016 ; Liu et al, 2014 ). Indeed, in other work by our group with analogous CNF composites at the same PTA loading, we found that pore volume increased by roughly 2-fold over the range of carbonization temperatures explored herein ( Hesterberg-Butzlaff et al, 2021 ; Hesterberg-Butzlaff et al, 2022 ), with greater extent of PTA volatilization at higher carbonization temperatures. The influence of CNTs is most easily discerned for CNF composites containing NF CNTs; despite there being no discernable difference in nanofiber diameter, these materials produced the largest measurable specific surface area via BET.…”
Section: Resultssupporting
confidence: 61%
“…S.3 ) ( Greenstein et al, 2021 ; Peter et al, 2016 ; Liu et al, 2014 ). Indeed, in other work by our group with analogous CNF composites at the same PTA loading, we found that pore volume increased by roughly 2-fold over the range of carbonization temperatures explored herein ( Hesterberg-Butzlaff et al, 2021 ; Hesterberg-Butzlaff et al, 2022 ), with greater extent of PTA volatilization at higher carbonization temperatures. The influence of CNTs is most easily discerned for CNF composites containing NF CNTs; despite there being no discernable difference in nanofiber diameter, these materials produced the largest measurable specific surface area via BET.…”
Section: Resultssupporting
confidence: 61%